Richards Bay zircon. - Pietersen, Kevin John. (2012)
Zircon from the zircon concentrate of Richards Bay Minerals was investigated with a view to understanding the morphology and provenance. The obsevations were applied to the reduction of uranium, thorium and other trace elements in the heavy mineral placer deposits. It is evident from differences in morphology, optical characteristics, cathodoluminescence, inclusion types and trace element analyses that the zircon is derived from numerous parent rocks. Rare earth element modelling reveals several possible parent rocks including rhyolites, granites, syenites, pegmatites and carbonatites. Fission track U mapping of individual zircons indicated an enrichment of U in the rims and grain terminations. The U maps were used to devise and test several methods, including abrasion and partial dissolution, to reduce the combined U and Th concentration from 450-563ppm to below 400ppm. The effect of magnetic cleaning, density separation and size classification of the zircon concentrate on the U +Th concentration was found to be negligible. Air abrasion and HF acid dissolution successfully reduced the U +Th concentrations to between 332 and 383ppm. The contribution of trace elements from inclusions, surface pit fillings and coatings, and foreign minerals within the zircon concentrate were evaluated by by scanning electron microscope identification. === Thesis (M.Sc.)-University of Natal, Durban, 1992.